ABORSI DALAM PERSPEKTIF HADITS RIWAYAT AHMAD BIN HANBAL NO 18989 - Ahnaf Nur Fauzan Romadhon; Tajul Arifin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This research was conducted because of the increasing cases of abortion in society which caused a shift in values, and in some cases, abortion was considered as a common thing. The purpose of this research is to discuss abortion in the perspective of the Hadith narrated by Ahmad bin Hanbal. This research was conducted using descriptive analytical methods and qualitative approaches, and referring to various relevant data sources. The results and discussion of the research are about the definition of abortion and its types, as well as the relevance of the Hadith narrated by Ahmad bin Hanbal no 18989 in Musnad Ahmad's book with abortion. This study concludes that according to the Hadith narrated by Ahmad bin Hanbal no 18989 abortion is included in semi-intentional killing because it fulfills the elements of semi-intentional killing and is an act that is prohibited and considered unlawful in Islam. However, research also states that abortion may be permissible under certain circumstances, such as when the life of a pregnant woman is threatened due to an abnormal condition of the fetus.